Integrated System Development for Digital Charity: Analyzing Media Communication in YouTube Marapthon Live Donations and Christian Sermon-Based Donations - Agnes Melliana Eviyanti; Gilbert Timothy Majesty; Amri Sinuraya (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2026)
This research examines digital charity practices within Christian media communication on YouTube, focusing on two distinct donation formats: marapthon live stream donations (e.g., 24‑hour fundraising events) and sermon‑based donations (offerings collected during or after online worship services). Despite the rapid growth of faith‑based online giving, a critical problem remains: the absence of an integrated system that aligns these two donation models with Christian values of transparency, accountability, and community stewardship. Existing platforms often treat live marapthon and sermon donations separately, leading to fragmented donor experiences and inefficient fund utilization. Therefore, this study aims to develop a conceptual framework for an integrated digital charity system by comparatively analyzing media communication strategies in both donation contexts. The proposed method is a netnographic comparative analysis, involving systematic observation of YouTube comments, chat logs, and video descriptions from 10 Christian channels (5 marapthon‑focused, 5 sermon‑focused) over six months, supplemented by semi‑structured interviews with content creators and donors. The main findings reveal that marapthon donations emphasize urgency and real‑time social proof, while sermon donations rely on theological framing and pastoral trust. The synthesis proposes a hybrid system architecture incorporating real‑time donation tracking, automated acknowledgment, and weekly theological reflection modules. In conclusion, integrating both models into a single development framework enhances donor engagement and aligns digital charity with Christian communication ethics, offering practical guidelines for church‑based YouTubers and platform developers.